BREAKTHROUGH IMMUNOMODULATION THERAPY IN IDIOPATHIC PULMONARY FIBROSIS: A NARRATIVE LITERATURE REVIEW - Amiruddin; Faridj Maulana Amir (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Background: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease with a poor prognosis. Several antifibrotics such as pirfenidone and nintedanib have been shown to slow the decline in lung function but cannot stop the ongoing or existing fibrosis process. Recent evidence suggests that immune dysregulation, including macrophage activation and PD-L1 expression on fibroblasts, plays a key role in the pathogenesis of IPF, thus encouraging the emergence of potential immunomodulation therapies. Methods: This paper attempts to review several English-language literature from 2015–2025 through PubMed, Scopus, and ClinicalTrials.gov. Articles relevant to immunotherapy, immunomodulators, or immune mechanisms in IPF were included, while non-scientific or non-immune-related publications were ignored. Results: A total of 15 primary publications were identified. Immunotherapy approaches such as PD-L1 inhibition, Treg activation, and IL-4/IL-13 blockade have shown antifibrotic and immunoregulatory effects. New agents such as the TNIK inhibitor (ISM001-055), the peptide LTI-03, and CAR-Treg therapy have shown promising early results in translational models and early-phase clinical trials. Conclusion: Immunotherapy has the potential to be a novel approach to IPF management by targeting the immune microenvironment. Further trials are needed to ensure safety and efficacy for long-term treatment.